KONSEP DAN KEPENTINGAN PENGADUAN AWAM DARIPADA PERSPEKTIF ISLAM DAN MODEN: SUATU SOROTAN LITERATUR: The Concept and Importance of Public Complaint from Islamic and Modern Perspective: A Literature Review - Zainuddin, Madihatun; Syed Ismail, Sharifah Hayaati (Jurnal Syariah, 2020)
This article discusses the concept and importance of public complaints (PC) as a result of a review of 22 literatures (2008-2019). It aims to identify what are the discussion of PC and how its importance from Islamic and modern perspectives in the literature. Public Complaints (PC) means grievances, comments or suggestions due to a customer›s dissatisfaction against public services delivery. It is one of the government essential mechanisms to identify problems and weaknesses in services and to produce best solution. In organization’s governance, especially in the century, the community views are important input. There are two main reasons for PC i.e., due to organization failure to provide the best service and also to resolve previous complaints. From the study it is found that the most discussed issues related to PC from Islamic perspective are on three aspects i.e., integrity, customer satisfaction and service quality. PC discussions from modern perspectives are often referred to four aspects include customer satisfaction, quality of service, the value of integrity and the need for continuous improvement. Literature review also found that an effective complaint handling system is important to create quality public service. The basis for Islamic literature discussions is from the Qur’ān, al-Ḥadīth, the concept of al-shūrā, amar ma‘rūf nahī munkar, maṣlaḥah, maqāṣid al-sharī‘ah, the value of trust and the views of scholars include Karim Zaidan, ‘Abd al-Wahhāb Khallāf, al-Bayḍawī and Raja Ali Haji. All 22 literatures agreed on the importance of PC in service delivery and the need for it to be resolved effectively. The literature also found that the lesser the PC the higher the service quality. And success in dealing with PC shows service provider commitment that can lead to a good service delivery culture.